THE EFFECT OF SERVICE QUALITY ON CUSTOMER SATISFACTION: STUDY ON THE CUSTOMERS OF MELODIA HOTEL IN POBIEROWO, POLAND - Rofiah, Tazqiyatur; Prabandari, Sri Palupi (Jurnal Ilmiah Mahasiswa FEB, 2014)
This study aims to examine the effect of Service Quality on Customer Satisfaction at Melodia Hostel in Pobierowo, Noth of Poland, Polandia. The regression analysis, F test and t test, were conducted in order to acknowledge the relationship among the independent variables (tangibility, reliability, responsiveness, assurance, and empathy) on Customer's Satisfaction. This study is explanatory research.  100 questionaire were distribute to Melodia's Hostel guest who were staying for more than two times in tree years. The sampling   technique  used   is  purposive   sampling   and   the   research   instruments  were   tested  using  the validity test, reliability test, and classical assumption test. The hypothesis testing used F test and t test in multiple   regression   analysis.  The   multiple   regression   showed   that   simultaneously   and   partially Tangibility,  Reliability,  Responsiveness,  Assurance,  and Empathy had significant  effect  on Customer's Satisfaction. The dominant test shows that Assurance has dominant effect on customer's satisfaction.Keywords:  service   quality,   tangibility,   reliability,   responsiveness,   assurance,   empathy,   customer satisfaction.